NONLINEAR AMPLITUDE EVOLUTION OF BAROCLINIC WAVE-TRAINS AND WAVE-PACKETS - Moroz, I; Brindley, J (1984)
The weakly nonlinear theory of baroclinic wave trains and wave packets is examined by the use of systematic expansion procedures in appropriate powers of a small parameter measuring the supercriticality according to linear theory; multiple scaling techniques are employed. Crucial importance is ascribed to the magnitude of parameters measuring dissipation and dispersion relative to each other and to the supercriticality, and equations describing the slow evolution in space and time of the wave amplitude are established for a range of parameter values. For vanishingly small dissipation the wave train equations have straightforward oscillatory solutions, dependent on initial conditions, and for large dissipation steady equilibration, independent of initial conditions, is predicted. For moderately small dissipation, however, a wide variety of behaviors is possible - including steady equilibration, single and multiple periodicity, and aperiodicity - in the solutions of the equations, which are recognizable as generalizations of the Lorenz attractor equations. Equations describing the evolution of wave packets take a variety of forms; for vanishingly small dissipation or for large dissipation, they are essentially parabolic and of nonlinear Schroedinger type, whilst for moderate dissipation they are of Lorenz type, modified by spatial variations. Solutions of a number of these equations are discussed and compared, where appropriate, with experimental results.